Peran Serikat Pekerja dalam Hal Perselisihan Hubungan Kerja yang Berdampak pada Pemutusan Hubungan Kerja - Enggartiasti Sherly Anggraini (Jurnal Syntax Admiration, 2023)
In every company, of course, always strive to create a cooperative and comfortable work environment for each worker. This study aims to analyze the role of trade unions in overcoming labor relations disputes that can have an impact on termination of employment. The research method raised in this study is Normative research. Normative Law Research is legal research conducted by examining library materials or secondary data".  The results showed that trade unions have a very important role in handling labor relations disputes that can have an impact on termination of employment. The role of trade unions includes being a mediator in dispute resolution, providing legal opinions and advice to members, and protecting workers' rights through negotiations and protests. The study recommends the need to increase the role of trade unions in addressing labor disputes that can have an impact on termination. This can be done through providing training and education to union members on labor relations law and the role of unions in resolving disputes. Thus, it is expected to create a more stable and conducive work environment for workers.